2003
DOI: 10.1097/00007435-200304000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Female Prisoners’ Preferences of Collection Methods for Testing for Chlamydia trachomatis and Neisseria gonorrhoeae Infection

Abstract: The study population of female federal prisoners expressed no aversion to the self-collection of either vaginal swab or urine specimens for STD testing. A majority of participants expressed a preference for noninvasive techniques rather than a pelvic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…These data are similar to those for our STD clinic population and those of Miller et al and Wendel et al (18,30,31). Male urine and SOVS have been shown to be acceptable for the detection of T. vaginalis (9,10,16,20,23,31). In our study, these self-obtained samples demonstrated a very high initial sensitivity and specificity for TMA of 96.7% and 97.3%, respectively, and the TMA assay had excellent resolved sensitivity and specificity at 98.6% and 99.1%.…”
supporting
confidence: 90%
“…These data are similar to those for our STD clinic population and those of Miller et al and Wendel et al (18,30,31). Male urine and SOVS have been shown to be acceptable for the detection of T. vaginalis (9,10,16,20,23,31). In our study, these self-obtained samples demonstrated a very high initial sensitivity and specificity for TMA of 96.7% and 97.3%, respectively, and the TMA assay had excellent resolved sensitivity and specificity at 98.6% and 99.1%.…”
supporting
confidence: 90%
“…Collection was not uncomfortable for 84.3% of the women, and a subanalysis of the question according to age showed that 87.4% of women 25 years or older (n ϭ 480) and 78.8% of those Ͻ25 years of age (n ϭ 212) reported that the collection process was not uncomfortable (P ϭ 0.005). These observations are similar to other studies assessing self-collection of vaginal samples using swabs (3)(4)(5)(6). Other studies have reported that self-collection of vaginal samples was not preferred over collection by health care workers (7-10) but was acceptable.…”
supporting
confidence: 88%
“…Similarly higher sensitivities have been observed with vaginal swab specimens than with urine and/or cervical swab specimens for the detection of C. trachomatis in other studies (32,34,40) and for the detection of N. gonorrhoeae (32,34). Many studies have shown that self-collection of vaginal swab specimens is well accepted by women (12,15,28) and that the results obtained with such specimens are comparably sensitive to those obtained with clinician-obtained vaginal specimens, making them the specimen type of choice for laboratory testing (5,12,15,32,40). The use of self-obtained vaginal swabs also allows women to be screened in nontraditional clinical settings, such as at street clinics, community sites, and home, thereby increasing the number of patients who can be tested (11,31).…”
Section: Discussionmentioning
confidence: 53%